PERAN RELIGIOUS DALAM KEPUTUSAN PEMBELIAN BUSANA MUSLIM SECARA ONLINE DI INDONESIA - Surajiyo Surajiyo; Ronal Aprianto (Strategic: Journal of Management Sciences, 2024)
This study aims to identify the role of religiosity values in online purchasing decisions for Muslim fashion in Indonesia. The method used in this research is a literature review, revealing that religiosity is a significant factor influencing consumer preferences. The findings indicate that several aspects of religiosity, such as adherence to religious teachings, religious symbols, and purchasing ethics aligned with Islamic values, have a significant impact on shaping purchasing decisions. The study also analyzes the most dominant religiosity factors, including spiritual commitment and the practice of religious teachings in daily life. Additionally, the research explains the meaning consumers assign to religious values in the purchasing process, where Muslim fashion is seen not only as a functional product but also as a symbol of religious identity and a means of strengthening spiritual connections. The findings of this study are expected to provide valuable insights for marketers to understand Muslim consumer motivations in the e-commerce context and offer guidance in developing effective marketing strategies based on religious value.